RESIDENTIAL-BUSINESS DESIGN WITH AN ENVIRONMENT-FRIENDLY ARCHITECTURAL APPROACH ON MEMPAWAH RIVERSIDE - Anisa Bayna, Insirra
The use of the river as a business space is something that is commonly done by the people on the banks of the Mempawah River. Two businesses are mostly run on the Mempawah River: the restaurant business and the canoe rental business. Both of these businesses showed a positive trend so the business increased in number. The need for space for businesses on the banks of the river makes the residences on the banks of the Mempawah River have a dual function as business spaces. The house is the place to run a household-based business.